ResoFox: A GUI-based tool for calculating resolution and relative intensity of neutron powder diffractometers - Chen, Li-Fang (SoftwareX, 2025)
ResoFox is a Python-based GUI tool for analyzing the resolution of neutron powder diffractometers based on the classical Caglioti model. It calculates FWHM, angular resolution, and relative intensity in diffraction patterns under various optical settings, and supports simulation of FCC and BCC diffraction patterns. Users can input key parameters via an intuitive interface, with real-time visual output. Benchmarking against theoretical plots and McStas confirms its accuracy. ResoFox aids early-stage instrument design, educational use, and communication between beamline scientists and users. A Windows standalone version is provided. This paper details the software’s features and validation through theory and Monte Carlo comparison.